Risk Analysis of Sino-American Military Conflict The Trends in China-US Military Relationship - Šetina, Martin; Maslowski, Nicolas, 1972-; Rolenc, Jan Martin, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The ascent of China to a global power status has created a new wave of theoretical discourse on what this means for the future of international relations. The general consensus on a unipolar order of international relations is slowly giving way to discourse. The time of polarity shift in the system is associated with a likely conflict between the descending hegemon and the ascending power (Snyder 2002; Mearsheimer 2010). This theoretical background suggest that in the future, we might witness a military conflict between the US and China. On the other side of the spectrum is a more optimistic view of China's rise, which emphasizes the role of economic interdependence and the extreme cost of any aggressive foreign policy that would escalate the conflict potential between China and the US (Ikenberry 2008; Kang 2007; Fravel 2010). This assumption of a future military conflict between the US and China is at the center of this research. In the following pages I will explore the idea of a military conflict between the US and China in an in-depth analysis of the most contested and conflict-prone issues between China and the US: the future of Taiwan and the Senkaku Island dispute.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses